Clinical validation of a novel bioluminescence imaging technology for aiding the assessment of carious lesion activity status. Issue 5 (10th March 2021) - Pitts, Nigel; Shanks, Neil; Longbottom, Christopher; Willins, Marjory; Vernon, Bruce
Abstract: Objectives: Clinical validation of a bioluminescence imaging system (Cis) as measured by the level of agreement between clinician visual and tactile assessment of carious lesion presence and activity and the presence/absence of elevated luminescence on a tooth surface determined from intraoral image mapping. Materials and Methods: This was a regulatory clinical study designed in consultation with the FDA. The design was a prospective, five‐investigator, nonrandomized, post‐approval, clinical study utilizing the Cis to provide images of elevated calcium ion concentration (indicative of active demineralization) on tooth surfaces via use of a photoprotein. Imaged teeth were identified as "sound" or having "active lesions." Images were scored independently for luminescence. Results: A total of 110 participants aged 7–74 years were imaged. Of the 90 teeth assessed as "sound, " 88 were deemed to show no luminescence by the reviewing investigator, a negative percentage agreement of 97.8% (significantly >50% agreement [ p < .0001]; one‐sided 97.5% confidence interval [CI]: 0.9220). Of the 86 teeth initially assessed as having an "active lesion, " 78 were deemed to show luminescence by the reviewing investigator, a positive percentage agreement of 90.7% (significantly >50% agreement [ p < .0001]; 97.5% CI: 0.8249). There were no patient‐related adverse events. Conclusions: Results show, with a high level of agreement, that Cis can differentiate tooth surfaces clinically identified as involving active enamel lesions (ICDAS code 2/3), from sound sites (biochemically equivalent to inactive lesions) and that the system is safe for clinical use.